Company's performance self-assessment (CoPSA) among facilities outsourcing firms in Malaysia: a focus on service delivery - Abdul Hamid Mar Iman; Muhammad Umbugala Douglas; Hishamuddin Mohd Ali (2015)
Company performance self-assessment (CoPSA), whose fundamental purpose is to provide a check-and-balance mechanism for practice performance through progress-and-performance self-assessment (PaPSa) is yet to be in place in the facilities management industry. Specially needed by facilities service outsourcing firms (FSOFs), CoPSA benefits the top management from organizational introspection of company's own performance. This paper proposes and tests a CoPSA model using a parametric approach. Managers’ perceptions about service delivery performance of their firm are measured using the likert scale and then deduced into a three-equation two-step recursive model. From a total of 207 randomly chosen Malaysian outsourcing firms, sixty responses were obtained. The results indicate that more than half of the sampled managers have envisioned high performance delivery, with 80% achievement as their goal. However, this has not been adequately supported by a coherent firm's internal structure. In view of the finding, the study concludes that the service delivery strategy of small fSofs in Malaysia is perceived to be rather passive.